Typotopia - Noorhaslina, binti Senin; mohamad faizuan, bin mat; mohamad zamhari, bin abolhasan; Siti Shahida, Kamel; Maizatul Nurhuda, bt. Saadon (2018)
Today’s learners mainly consist of those who are born or brought up during the digital era where they are used to the Internet and gadgets from an early age. Hence, it becomes a challenge as an educator to keep up with the students’ different learning styles and expectation. Currently, there are multiple available games and websites for typography, but most are in 2D form and only available through their own website. WHAT IS TYPOTOPIA? TYPOTOPIA is an educational mobile apps to enhance learning experience for Typography course through Augmented Reality (AR). WHY AUGMENTED REALITY (AR)? Augmented Reality is considered as one of the promising technology of the future and it should be explored as part of teaching and learning.